Failure Investigation of Blank Holder Force (BHF) Control in The Outside Bracket For Front Seat - Rofan Yulian Romansyah; Hanif Azis Budiarto; Yuliar Yasin Erlangga; Yunita Nugrahaini Safrudin (Journal of Applied Engineering and Technological Science (JAETS), 2023)
This study investigated the failure of the Blank Holder Force (BHF) control in the outside bracket for the front seat. The production process involved progressive dies consisting of nine stations: first pierce, first trim, second trim, idle, flange, idle, second pierce, idle, and parting. However, at the 7th-9th station, the pilot hole in the product deforms into an oval shape, which is undesirable. Gemba-Kaizen methods were used in this study, and primary data were collected by comparing the design and actual progressive dies. The results showed that product defects are primarily caused by an unbalanced BHF and inadequate piercing clearance. A uniform distribution of force during the forming process is obtained by reducing the spring number on the blank holder. This reduces the force generated during the process. Furthermore, the die clearance was increased from 0.01 mm to 0.1 mm, making press and die alignment less critical and requiring less cutting and stripping forces